Anticancer Activities of Bromelain Hydrolysate of Soy Protein Against Breast Cancer Cells MCF-7 - Hermanto, Sandra; Nurgraha, Auliyah Aisyah; Rudiana, Tarso (Jurnal Kimia Valensi, 2024)
Soybeans contain proteins that have the potential to produce anticancer bioactive peptides. This study aims to determine the anticancer activity of soy protein hydrolysate against MCF-7 breast cancer cells. Soybean protein hydrolyzed by bromelain enzyme 0.5% (w/v) at the optimum temperature and pH for protein hydrolysis using the Bergmeyer and Grassl method. The degree of hydrolysis value of protein hydrolysate was determined by the Alder-Niesen method and the protein profile was analyzed by SDS-PAGE. The hydrolysate with the best degree of hydrolysis value was analyzed for anticancer activity against MCF-7 breast cancer cells by the Presto Blue assay method, and fractionation of protein hydrolysates by gel filtration chromatography (Sephadex G-15). The molecular weight of the peptide was characterized by LCMS/MS. Soy protein hydrolysis using 0.5% (w/v) bromelain enzyme was optimum at 65 ºC and pH 7.0 for 4 hours, with a hydrolysis degree value of 20.57%. The SDS-PAGE analysis showed that the protein hydrolysates had quite thick protein bands in the range of <35 kDa with an IC50 value of 70.37 mg/mL. Based on the LCMS/MS results, the peptide from fractionation has a molecular weight of 5.133 kDa.